Association of lip print and sex among Nigerians - Adamu, Lawan; Taura, Magaji; Hamman, Wilson; Ojo, Samuel; Dahiru, Ahamd; Sadeeq, Abubakar; Ibrahim, Aliyu (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background: The use of prints as a mean of personal identification is one of the common methods in forensic anthropology and the most popular prints are fingerprints. The second print of interest is lip prints, which are normal lines and fissures in the form of wrinkles and grooves present in the zone of transition of human lip. The study was aimed to determine association of lip prints types and sex among Nigerian population. Materials and Methods: A total of 820 subjects (414 males and 406 females) participated in the study. The lip prints were obtained on microscopic glass slide and developed using carbon black powder, after which the print was divided into 10 quadrants and analyzed using magnifying lens. The data were analyzed using Chi-square test andP< 0.05 was considered as level of significance. Results: The result shows the percentage distribution of lip prints in males with highest prevalence of type V (31.28%) and the least of type I’ (0.55%). In females type V (31.50%) was predominant while the least was type I’ (0.59%). The statistically significant association of lip prints types with sex in all the lip quadrants (P< 0.001) was found, except in lower right lateral (LRL) and upper median (UM0) quadrants. Conclusion: The lip print was found to be statistically associated with sex. Hence, lip prints can hold potential promise as supplementary tool in personal identification.